Methodology of QT‐Interval Measurement in the Modular ECG Analysis System (MEANS) - Kors, Jan A. (Ann Noninvasive Electrocardiol, 2009)
Background: QT prolongation as can be induced by drugs, signals the risk of life‐threatening arrhythmias. The methodology of QT measurement in the modular ECG analysis system (MEANS) is described. Methods: In the simultaneously recorded leads of the standard 12‐lead electrocardiogram (ECG), the QRS complexes are detected by a spatial velocity function. They are typed as dominant or nondominant, and a representative complex per lead is obtained by averaging over the dominant complexes. QRS onset and T end are determined by a template technique, and QT is measured. MEANS performance was evaluated on the 125 ECGs of the common standards for quantitative electrocardiography (CSE) multilead database, of which the waveform boundaries have been released. Results: MEANS detected correctly all 1445 complexes of the CSE library, with one false‐positive detection due to a sudden baseline jump. All dominant complexes were correctly typed. The average of the differences between MEANS and reference was less than 2 ms (=1 sample) for both QRS onset and T end, and 2.1 ms for QT duration. The standard deviation of the differences was 3.8, 8.4, and 10.4 ms, respectively. Conclusions: A standard deviation of 10.4 ms for QT measurement seems large when related to the regulatory requirement that a prolongation as small as 5 ms should be detected. However, QT variabilities as encountered in different individuals will be larger than when measured in one individual during pharmacological intervention. Finally, if the U wave is part of the total repolarization, then T and U form a continuum and the end of T becomes questionable.